Trends and Effectiveness of ICT Interventions for the Elderly to Reduce Loneliness: A Systematic Review - Choi, Hee Kyung (Healthcare (Basel), 2021)
Elderly people are sensitive to loneliness, which may contribute to mental and physical health, serious illness, and increased mortality. This study investigates the development trend of information communication technology (ICT) interventions designed for the elderly to reduce loneliness and synthesize its effect. We searched relevant articles on 23 May 2020 using three databases: Ovid-Medline, Ovid-EMBASE, and the Cochrane library. Data extraction and quality assessment were independently performed by two authors. The development is changing from animal robots to online social platforms and from simple emotional support to a multifaceted system that promotes social participation, cognition, physical activity, and nutrition. Our systematic review reported that ICT interventions are being developed to alleviate loneliness and increase social participation. Our study revealed an increase in the use of ICT interventions among the elderly and a positive change in their attitude toward ICT interventions. ICT interventions in the field of nursing should continue to be developed in the future to meet social, health, and safety needs. In the context of coronavirus disease 2019 (COVID-19), ICT interventions are needed to respond effectively to the needs of the elderly. This study is expected to provide basic knowledge for the development of ICT interventions for the elderly.